ANALYSIS OF THE LINGUISTIC LANDSCAPE OF NAKULA STREET SIGN IN SEMINYAK, BALI - Rofi Ardiansyah; Agustinus Hary Setyawan (Bajang Institute, 2025)
This study analyzes the use of language on signs along Nakula Street in Seminyak, Bali, an area known as an international tourist destination. The purpose of this study is to identify the dominant language types used on the signs and to analyze the creative linguistic devices employed to attract attention. Data from 118 signs were collected through virtual documentation using Google Maps Street View. The results show that the majority of the signs (66.95%) are monolingual, with English being the most dominant language (50.83%). Bilingual signs (32.20%) often combine Indonesian and English. In addition, various linguistic devices such as code-mixing, transliteration, and slang were also found. These language choices reflect business owners' strategies to communicate with international tourists while maintaining local cultural identity. This study provides a deeper understanding of how language in public spaces can reflect identity, culture, and commercial goals in a multicultural tourism environment